2017
DOI: 10.1016/j.agee.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and selection of indigenous Bradyrhizobium strains with outstanding symbiotic performance to increase soybean yields in Mozambique

Abstract: HighlightsBiological nitrogen fixation (BNF) is a key process for soybean production in Africa.The selection of elite African indigenous soybean Bradyrhizobium strains is a feasible strategy.Eighty-seven isolates were obtained from soybean nodules in Mozambique.Isolates fit into the Bradyrhizobium (75%) and Agrobacterium-Rhizobium (25%) clades.Five Bradyrhizobium isolates with outstanding symbiotic performance were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 66 publications
(105 reference statements)
8
71
0
2
Order By: Relevance
“…Like most legumes, the N 2 -fixing trait of cowpea confers adaptation to low nutrient soils, with some genotypes deriving up to 96% of their nitrogen (N) requirements from symbiosis, which often leads to significant N contribution to cropping systems and grain yield increases [1] [4] [5]. However, due to variations in legume symbiotic performance resulting from genotypic differences and N 2 -fixing efficiency of the rhizobial symbionts, there is often the need to screen for improved N 2 fixation among legume germplasm [6] [7]. Of the many techniques used to estimate legume symbiotic performance, the 15 N natural abundance has so far been useful in quantifying N 2 fixation in field-grown legumes [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Like most legumes, the N 2 -fixing trait of cowpea confers adaptation to low nutrient soils, with some genotypes deriving up to 96% of their nitrogen (N) requirements from symbiosis, which often leads to significant N contribution to cropping systems and grain yield increases [1] [4] [5]. However, due to variations in legume symbiotic performance resulting from genotypic differences and N 2 -fixing efficiency of the rhizobial symbionts, there is often the need to screen for improved N 2 fixation among legume germplasm [6] [7]. Of the many techniques used to estimate legume symbiotic performance, the 15 N natural abundance has so far been useful in quantifying N 2 fixation in field-grown legumes [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hungria et al [19] also reported that inoculation of soybean significantly increased the nodule number over the control. Attempts realized in Mozambique were also found that some indigenous rhizobia were effective than five reference strains used in the country to improve soybean production [20]. Unlike Doko and Piramama varieties, local rhizobia were unable to increase the number of nodules on Canarana compared IRAT FA3 excepted RSC119, which induced nodules production like the latter.…”
Section: Impact Of Indigenousrhizobia On Nodule Number and Nodule Drymentioning
confidence: 99%
“…In order for a rhizobial strain to serve as an effective agricultural inoculant, it must be able to (i) fix large amounts of nitrogen and (ii) effectively outcompete the indigenous rhizobial population for nodule occupancy. Unfortunately, the native rhizobial community that is often the most competitive for nodule occupancy tends to exhibit low N 2 fixation rates (for example see A.A. Cardoso et al 2017;Chibeba et al 2017). Indeed, for decades the failure of rhizobia to improve crop yields has often been attributed to the poor competitive abilities of the inoculant and not to poor N 2 fixation abilities (Triplett and Sadowsky 1992;Streeter 1994;Ndungu et al 2018).…”
Section: Synthetic Biology Approaches To Engineering the Symbiosismentioning
confidence: 99%